UPAYA PENINGKATAN PERAN ORANG TUA SISWA TERHADAP PENDIDIKAN SEKS PADA ANAK USIA 4-6 TAHUN - Wahyuni, Santi; ., Badriah; Cahyati, Yanti (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2021)
Limited knowledge, shame and taboo when talking about sex in children causes parents to play a less active role in sex education. As a result, children have wrong perceptions, deviant sexual behavior and an increase in cases of sexual violence. The purpose of community service is to increase the understanding and ability of parents in providing sex education from an early age. The activity begins with the identification of the role and assessment of the understanding of the students' parents. The core activities are psychoeducation about sex development, sex education and prevention of sexual violence against children, assistance activities through simulation practice and roleplay to provide information on sex education. The results of the evaluation of cognitive aspects showed that the majority of participants' level of knowledge before psychoeducation was sufficient (75%) and after being given psychoeducation 75% of participants had good knowledge. The psychomotor aspect found that the majority of participants (75%) were able to provide information on sex education to their children directly and 25% were in the sufficient category. The conclusion is that there is an increase in the knowledge and ability of students' parents in providing sex education to their children. Keywords: the role of parents, sex education